Evaluasi Stimulasi Hydraulic Fracturing Dan Analisa Produktivitas Sumur Pada Formasi Sandstone Sumur ”MG-09” Lapangan ”FI” - Aly Rasyid; Nugroho Marsiyanto; M Gilang Farhana Irsyad (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
Hydraulic fracturing is a stimulation method by injecting treatment fluid to fracture a formation by using proppant (sand) as a fracture buffer media which aims to improve the production rate in the well. Fracture geometry evaluation is done to get the right fracture geometry value. In the production evaluation, using the Howard and Fast method, the Kavg value in the MG-09 well was 39.4094 mD. Based on the actual production rate after hydraulic fracturing in well MG-09 there was an increase in the total flow rate from 65 BLPD to 182 BLPD. Based on the calculation of the increase in Productivity Index, the Prats method obtained an increase in PI of 2.63 times, while the CSD method (Cinco-ley, Samaniego and Dominique) obtained a multiple of the increase in productivity (K2P) or an increase in PI of 2.63 times and the skin factor of +12 to -4.8 Based on the comparison of the three-phase IPR curve of the Pudjo-Sukarno method, where at the same Pwf of 400 psi there was an increase in oil production from 45 BOPD to 134 BOPD. Therefore, the results of the hydraulic faracturing evaluation of the MG-09 well in terms of the work process (proppant, fracturing fluid), production analysis (permeability, productivity index, increased productivity index of the prats and CSD methods, level of skin repair and IPR curve analysis) were declared successful.